Profesionalisme Guru Agama Kristen dalam Membina Jemaat - Arozatulo Telaumbanua (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Education in congregations is often characterized by the lack of exemplary Christian teachers who teach, foster, and educate them. This example is closely related to the professionalism of Christian teachers in fostering congregations in a consistent, dynamic, effective, and enjoyable way. The professionalism of Christian teachers in teaching and nurturing congregations is the key to bringing the congregation to the perfection of life like Christ. The life and character of the Christian religion teacher greatly influence the life and character of the congregation. A Christian teacher who teaches and nurtures congregations must have a spiritual experience with God have the ability of knowledge, skills, and ability to use methods in the learning process. The method of fostering congregations is one of the most professional teachers of Christianity in fostering a very strategic congregation. Because with this ability, it is possible for Christian religious teachers to be able to bring influence to the quality and spiritual life of the church. Thus, the church has the knowledge of faith in the truth of God, which is able to understand the truth well, has a character like the Lord Jesus Christ, which is to love and serve and have the values of Christ that are applied in everyday life. AbstrakPendidikan dalam jemaat seringkali diwarnai dengan kurangnya keteladanan guru agama Kristen yang mengajar, membina dan mendidik mereka. Keteladanan ini berkaitan erat dengan keprofesionalan guru agama Kristen dalam membina jemaat secara konsisten, dinamis, efektif dan menyenangkan. Profesionalisme guru agama Kristen dalam mengajar dan membina jemaat menjadi kunci dalam membawa jemaat kepada kesempurnaan hidup seperti Kristus. Kehidupan dan karakter guru agama Kristen sangat mempengaruhi kehidupan dan karakter jemaat. Seorang guru agama Kristen yang mengajar dan membina jemaat harus memiliki pengalaman rohani dengan Tuhan, memiliki pengetahuan, keterampilan dan kemampuan menggunakan metode dalam proses pembelajarannya. Metode dalam membina jemaat salah satu keprofesionalan guru agama Kristen dalam membina jemaat yang sangat strategis. Sebab dengan kemampuan ini, maka dimungkinkan guru agama Kristen mampu membawa pengaruh terhadap kualitas dan kehidupan rohani jemaat. Dengan demikian, jemaat memiliki pengetahuan iman akan kebenaran Allah, yakni mampu memahami kebenaran dengan baik, memiliki karakter seperti Tuhan Yesus Kristus, yaitu mengasihi dan melayani serta memiliki nilai-nilai Kristus yang diterapkannya dalam hidup sehari-hari